Exploring opportunities to scale out CSA in CSV through innovative business models - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Presented in September 2015 at CSV Workshop, India by Annemarie Groot and Jaclyn Rooker (Wageningen)